2021
DOI: 10.1007/s10071-021-01492-6
|View full text |Cite
|
Sign up to set email alerts
|

Social context shapes cognitive abilities: associative memories are modulated by fight outcome and social isolation in the crab Neohelice granulata

Abstract: Cognitive abilities of an animal can be influenced by distinct social experiences. However, the extent of this modulation has not been addressed in different learning scenarios: are all tasks similarly affected by social experiences? In the present study, we analyzed the effect of social dominance in aversive and appetitive memory processes in the crab Neohelice granulata . In addition, we studied the influence of social isolation on memory ability. Social dominance experiments consisted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 108 publications
0
2
0
Order By: Relevance
“…It was already known that the presence of adults during development is important for social functioning such as the regulation of aggression and appropriate dominance hierarchy structuring (Slotow et al, 2000;Bourjade et al, 2008Bourjade et al, , 2009Perré et al, 2002). A recent study on a crab species (Neohelice granulata) demonstrated that social isolation has a negative effect on longterm memory retention of both aversive or appetitive tasks (Santos et al, 2021). However, here we show that even the social motivation for conspecific cues can be affected, although the birds had been raised in a group and were isolated at the time of testing.…”
Section: Discussionmentioning
confidence: 99%
“…It was already known that the presence of adults during development is important for social functioning such as the regulation of aggression and appropriate dominance hierarchy structuring (Slotow et al, 2000;Bourjade et al, 2008Bourjade et al, , 2009Perré et al, 2002). A recent study on a crab species (Neohelice granulata) demonstrated that social isolation has a negative effect on longterm memory retention of both aversive or appetitive tasks (Santos et al, 2021). However, here we show that even the social motivation for conspecific cues can be affected, although the birds had been raised in a group and were isolated at the time of testing.…”
Section: Discussionmentioning
confidence: 99%
“…Belonging to a social group may also have beneficial effects on cognitive performance, as shown in wild as well as captive‐reared birds (Ashton et al ., 2018; Langley et al ., 2018), crabs (Santos et al . 2021) and fish (Brandão et al ., 2015; Ausas et al . 2019), but effects are not ubiquitous in the animal kingdom ( e.g ., Riley et al .…”
Section: Introductionmentioning
confidence: 99%